Burkitt’s lymphoma of mandible in a young Pakistani boy: a case report - Nabeela Riaz; Tooba Saeed; Mujtaba Nadeem (Journal of the Pakistan Medical Association, 2021)
Abstract In this part of world, Burkitt’s lymphoma (BL) of mandible considers a unique entity, while BL involving the jaw is endemic in Africa. BL being one of the most speedily growing malignancy, can cause immense destruction in maxillofacial region. This case report highlighted a 3 year child affected with BL of mandible. The presented complaint of the patient was a rapidly enlarging swelling on the right side of the face, causing disfigurement and interfering the normal oral functions. Confirmatory diagnosis of BL was established after correlating the clinical, radiographic, and biopsy features. Later on tumor board discussion held for this case, and the child underwent chemotherapy. Unfortunately, he could not survive after the second cycle of chemotherapy. Continuous....